1997
DOI: 10.1149/1.1837355
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Anodic Etching of Gallium Nitride

Abstract: The first study of photo-assisted anodic etching of unintentionally doped n-GaN at room temperature is reported here. The electrolyte used is a mixture of buffered aqueous solution of tartaric acid and ethylene glycol.The etching rate varies from -20 A/mm to as high as 1600 A/mm. A systematic study shows that (I) the etch rate, as well as the surface roughness, increases with the current density; (ii) the etching rate is the highest when the pH of the electrolyte is -7; and (iii) the etching is faster when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…The rates fall-off dramatically at high molarities (≥ 0.1M), most likely due to excessive oxidation of the surface. This effect is also seen with KOH solutions under the same conditions [21][22][23].…”
Section: /T (K)mentioning
confidence: 65%
See 1 more Smart Citation
“…The rates fall-off dramatically at high molarities (≥ 0.1M), most likely due to excessive oxidation of the surface. This effect is also seen with KOH solutions under the same conditions [21][22][23].…”
Section: /T (K)mentioning
confidence: 65%
“…The first photoenhanced wet etching of GaN at room temperature was reported using HCl/H 2 O and KOH/H 2 O solutions with He-Cd laser illumination [15]. Subsequently the Adesida group and others [16][17][18][19][20][21][22][23][24] employed broad-area Hg lamps and solutions of KOH, aqueous H 3 PO 4 or tartaric acid/ethylene glycol to achieve maximum room-temperature etch rates typically in the range 1000-2000Å·min -1 . In some cases the etched surfaces are smooth, but a more general result is the appearance of very rough microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent development is the demonstration of photoelectrochemical (PEC) wet etching which has resulted in significantly higher etch rates for GaN [44][45][46][47][48][49][50][51][52][53]. The PEC process utilizes photogenerated electron-hole pairs to enhance oxidation and reduction reactions taking place in an electrochemical cell.…”
Section: Photoelectrochemical Wet Etchingmentioning
confidence: 99%
“…Lu et al [48] reported on photo-assisted anodic etching of n-GaN in solutions of tartaric acid/ethylene glycol at room temperature. Etch rates as high as 160 nm/min were obtained for Hg arc lamp illumination of ~ 60 mW/cm 2 .…”
Section: Photoelectrochemical Wet Etchingmentioning
confidence: 99%
“…6 Photoenhanced electro-chemical (PEC) wet etching has also been demonstrated for etching of GaN. [7][8][9][10] PEC etching has the advantage of low surface damage and low equipment cost, but a method for producing smooth vertical sidewalls by this method has not yet been found. Recently, a two-step process including crystallographic wet chemical etching has been demonstrated for n-type GaN.…”
Section: Introductionmentioning
confidence: 99%